Indirect modulation of sensitivity to 5-fluorouracil by microRNA-96 in human colorectal cancer cells - Kim, Sun-Ah; Kim, Injung; Yoon, Sungjoo Kim; Lee, Eun Kyung; Kuh, Hyo-Jeong (Archives of pharmacal research, 2015)
5-FU is an anticancer drug that is widely used to treat cancers, including colorectal cancer (CRC); however, chemoresistance to 5-FU remains an important problem to be resolved. The role of microRNAs (miRs) in chemosensitivity has recently been studied in the development of therapeutic strategies to overcome drug resistance. Here, we focused on miR-96, which has been reported to demonstrate chemosensitivity. We investigated whether 5-FU sensitivity may be modulated by miR-96 in monolayer cells and whether this relationship also applies for drug resistance in 3D tumor spheroids (TSs). When the level of miR-96 increased, the expression of the anti-apoptotic regulator XIAP and p53 stability regulator UBE2N decreased, resulting in increased apoptosis and growth inhibition following 5-FU exposure. Transfection of miR-96 inhibitors resulted in an overexpression of XIAP and UBE2N, yet only minimal change was induced in apoptosis. Nonetheless, luciferase assay failed to show direct interactions between miR-96 and these genes. In TSs, 5-FU resistance corresponded to a significantly lower level of miR-96, however only XIAP, not UBE2N, was up-regulated demonstrating partial agreement with the 2D condition regarding target expression. Overall, these results suggest that miR-96 may modulate 5-FU sensitivity in CRC cells by promoting apoptosis; however, differential expression of target genes in TSs warrants further studies on the 5-FU resistance mechanism under 3D conditions.